THE INFLUENCE OF PORES SIZE AND TYPE OF AGGREGATE ON CAPILLARY HEAT AND MASS TRANSFER IN POROUS - Ismail, Nova Risdiyanto; Soeparman, Sudjito; Widhiyanuriyawan, Denny; Wijayanti, Widya (Journal of Applied Engineering Science, 2019)
An experimental study has been held to analyze the capillary-driven flow and evaporation process in porous media. Five different types of porous media had been chosen, namely concrete consisted river sand with the particle size of 0.125 and 0.250 mm, ferrous sand concrete with particle size of 0.125 and 0.250 mm, and natural stone as the comparison material. Top side of the specimens was exposed in a heater with 18.2 W, 27.3 W and 36.4 W. The bottom side of specimen was exposed in seawater which flowed capillary and evaporated. The value of thermal conductivity and porosity in porous media greatly affect the temperature distribution caused by the heat transfer process. Specimens with smaller particle size has a higher thermal conductivity which resulting in a larger heat transfer rate. Concrete with ferrous sand as aggregate has a better heat transfer rate than river sand specimen. The largest heat transfer rate obtained in concrete with 0.125 mm ferrous sand with the value of 0.256 W, 0.402 W and 0.524 W in every power addition. The rate of mass transfer value equals to the rate of evaporation that occurs and strongly depends on the capillary force of each specimen. The evaporation rate data is proportional to the heat transfer rate of each specimen. However the natural stone specimen has a higher evaporation rate than expected due to better interconnectivities between its channels.
Keywords: Porous media; heat transfer; evaporation rate; seawater